Phytoextraction to promote sustainable development - Anderson, C W N (Brawijaya University, 2013)
Mining makes a positive contribution to the economy of Indonesia. Significant earnings accrue through the export of tin, coal, copper, nickel and gold. Of these commodities, gold carries the highest unit value. But not all gold mining is regulated. Indonesia has a significant Artisanal and Small Scale Gold Mining (ASGM) industry, defined as any informal and unregulated system of gold mining. These operations are often illegal, unsafe and are environmentally and socially destructive. New technology is needed to support the sustainable exploitation of gold and other precious metal resources in locations where ASGM is currently practised. This technology must be simple, cheap, easy to operate and financially rewarding. A proven option that needs to be promoted is phytoextraction. This is technology where plants are used to extract metals from waste rock, soil or water. These metals can subsequently be recovered from the plant in pure form, and sold or recycled. Gold phytoextraction is a commercially available technology, while international research has shown that phytoextraction will also work for mercury. In the context of ASGM operations, tailings could be contained in specific ‘farming areas’ and cropped using phytoextraction technology. The banning of ASGM operations is not practicable or viable. Poverty would likely become more extreme if a ban were enforced. Instead, new technology options are essential to promote the sustainable development of this industry. Phytoextraction would involve community and worker engagement, education and employment. New skills in agriculture created through application of the technology would be transferrable to the production of food, fibre and timber crops on land adjacent to the mining operations. Phytoextraction could therefore catalyse sustainable development in artisanal gold mining areas throughout Indonesia.